2017
DOI: 10.1186/s12986-017-0170-x
|View full text |Cite
|
Sign up to set email alerts
|

High-cholesterol diet does not alter gut microbiota composition in mice

Abstract: IntroductionWestern diet containing both saturated fat and cholesterol impairs cardio-metabolic health partly by modulating diversity and function of the microbiota. While diet containing only high fat has comparable effects, it is unclear how diets only enriched in cholesterol impact the microbiota. Therefore, we aimed to characterize the response of host and microbiota to a high cholesterol (HC) diet in mice susceptible to cardio-metabolic disease.MethodsLDLR knockout mice received either 1.25% HC or no chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
(42 reference statements)
4
21
0
Order By: Relevance
“…A meta-analysis showed that the decrease of Turicibacter is consistent with increased inflammation in obesity (Jiao et al, 2018). In addition, the decrease in Turicibacter has been associated with abundant dietary cholesterol and dietary fat (Everard et al, 2014;Zhong et al, 2015;Dimova et al, 2017). We found that both high and low doses of BBR enriched the abundance of Turicibacter, and the effect was significant and more pronounced at the high dose.…”
Section: Discussionmentioning
confidence: 57%
“…A meta-analysis showed that the decrease of Turicibacter is consistent with increased inflammation in obesity (Jiao et al, 2018). In addition, the decrease in Turicibacter has been associated with abundant dietary cholesterol and dietary fat (Everard et al, 2014;Zhong et al, 2015;Dimova et al, 2017). We found that both high and low doses of BBR enriched the abundance of Turicibacter, and the effect was significant and more pronounced at the high dose.…”
Section: Discussionmentioning
confidence: 57%
“…Dimova et al . showed that Turicibacter increased in mice fed a high-fat diet 38 . However, two studies reported a decrease in Turicibacter in mice in response to high-fat feeding 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of vegans, slight changes in the anaerobic bacterial genera ( Bifidobacterium , Bacteroides , and Clostridium ) have been observed compared to omnivorous subjects . However, the available data seem to be controversial, since no differences in the gut microbiota of vegetarian and omnivorous Slovak subjects have been found, and the levels remained stable after a high cholesterol diet in a murine study . Other authors have also evaluated the influence of PS upon the gut microbiota in the context of a clinical trial in which 13 healthy subjects received during 3 weeks a control or plant stanol ester‐enriched margarine (3 g a day of plant stanols) – no differences being observed in gut microbiota composition compared to control group …”
Section: The Relationship Between Dietary Sterols and Gut Microbiotamentioning
confidence: 99%